1944
DOI: 10.2307/1538341
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine and Tetrahymena

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1945
1945
1972
1972

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…There can be no doubt as to the stimulatory effect of riboflavin, and it is altogether possible that it may function as a detoxifying agent as well. The detoxifying action of thiamine has been suggested previously in this connection (Kidder and Dewey, 1944).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…There can be no doubt as to the stimulatory effect of riboflavin, and it is altogether possible that it may function as a detoxifying agent as well. The detoxifying action of thiamine has been suggested previously in this connection (Kidder and Dewey, 1944).…”
Section: Discussionmentioning
confidence: 68%
“…Added carbon sources appear to be unnecessary except as they may perform a sparing action on the amino acids. Inorganic salts certainly are essential (Hall and Cosgrove, 1944;Kidder and Dewey, 1944) although the question of which elements need to be included is yet to be determined. The commonly employed inorganic salts usually accepted as being physiologically important satisfy the ciliate requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is apparent that, although Tetrahymena does possess the ability to synthesize thiamine, this vitamin is a potent stimulant to reproduction, size (Kidder and Dewey, 1944), and longevity (Johnson and Baker, 1943). Thiamine must, therefore, be included in complete media for this ciliate, but the amount needed appears to be less than has been previously used (Hall and Cosgrove, 1944;Kidder and Dewey, 1942;1944).…”
Section: Discussionmentioning
confidence: 99%
“…They reported growth of their strain of Tetrahymena in heat-and alkali-treated casein in the presence of thiamine and not in its absence. This criticism was shown to be invalid (Kidder and Dewey, 1944) when an extension of the earlier studies was carried out, using heat-and alkali-treated base media (casein, casein hydrolysate, gelatin, gelatin hydrolysate). It was then found that heat and alkali treatment of 1 Aided by grants from the Morgan Edwards Fellowship Fund,…”
mentioning
confidence: 98%